2020
DOI: 10.1371/journal.pone.0233392
|View full text |Cite
|
Sign up to set email alerts
|

Corneal donation for research versus for transplantation: A-year prospective study of acceptance rates in a French University Hospital

Abstract: Fresh corneal donation is essential for basic and preclinical research, but more unknown to public and the medical teams than donation for transplantation: it may raise concerns. We prospectively compared the acceptance rates and the characteristics of targeted corneal donation for research versus donation for transplantation during one year. The Agence de la Biomé decine authorized us to procure fresh corneas targeted for research, only from the donors with medical contraindications for transplantation, in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Notably, researchers in France concluded that targeting for research consent did not have a negative impact on clinical donations; thereby, research and clinical donation can potentially be an avoided competition. 10 Below is a summary of the current whole globe for research sourcing framework in the US.…”
Section: Sourcing Whole Globes For Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, researchers in France concluded that targeting for research consent did not have a negative impact on clinical donations; thereby, research and clinical donation can potentially be an avoided competition. 10 Below is a summary of the current whole globe for research sourcing framework in the US.…”
Section: Sourcing Whole Globes For Researchmentioning
confidence: 99%
“…Importantly, the longitudinal research consent approach provides globe access in the research arena before and after death, noting that some of these globes could never be destined for clinical use due to the prior involvement of an investigational device/surgical intervention. Notably, researchers in France concluded that targeting for research consent did not have a negative impact on clinical donations; thereby, research and clinical donation can potentially be an avoided competition . Below is a summary of the current whole globe for research sourcing framework in the US.…”
Section: Sourcing Whole Globes For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In this aspect, there is a frequent desire to collect other tissue types, such as retina, or donors with a particular characteristic including age, sex and type of disease or disease stage 37 . In an ideal world, procurement of research tissues would be collected specifically as ‘tissue for research purposes’ rather than a tissue collected for transplantation but then relegated to research due to safety or quality concerns 38 . The volume or availability of tissue required for timely completion of a research project may also go above and beyond the capabilities of what an eye bank can meaningfully supply without leading to delays 13 …”
Section: Sources Of Needmentioning
confidence: 99%